Study on Fire Resistance Ability and Mechanical Properties of Composites Based on Epikote 240 Epoxy Resin and Thermoelectric Fly Ash: An Ecofriendly Additive - Tuan Anh Nguyen; Quang Tung Nguyen; Xuan Canh Nguyen; Van Hoan Nguyen (Journal of Chemistry)
In this study, fly ash was tested as a filler in epoxy with concentrations of 5, 10, and 20 wt.%. Fly ash particles were modified by chemical treatments (using NaOH and HCl) to enhance the compatibility and adhesion, making mechanical properties and flame retardancy of materials better. Flexural strength, tensile strength, and impact resistance decrease as fly ash content increases. The compressive strength is further increased by the addition of fly ash (compressive strength of the materials including 5, 10, 20 wt.% of fly ash modified with NaOH is 176.01, 189.90, and 197.07 MPa, respectively). The interface between fly ash and epoxy matrix plays an important role in determining the mechanical strength and flame retardancy of synthetic materials. The results of UL-94HB and LOI test method for composite materials including 20 wt.% fly ash (modified by NaOH) reached 13.45 mm/min and 22.4%, respectively. These results showed that fly ash is an efficient additive as a flame retardant which decreases the amounts of additives in products and improves their efficiency. Fly ash was also dispersed into epoxy resin to enhance its resistance to oxidation.